An Application of Boundary Organisation Theory to Develop Landscape‐scale Conservation in Formal Agri‐environment Schemes. Issue 1 (15th October 2014) - Franks, Jeremy R.
Abstract: Recent reviews of UK biodiversity conservation have emphasised the need to adopt a landscape‐scale approach. This study reports the problems encountered by farmers currently participating in landscape‐scale conservation options in a UK agri‐environment scheme. Many of these problems were overcome with the assistance of independent organisations working as intermediaries between farmers and between farmers and government agencies. Findings from two surveys of farmers not involved in landscape‐scale conservation in agri‐environmental schemes reveal the problems they expect to encounter to be similar to those faced by farmers with experience of successful collaboration. It is therefore likely prospective collaborators would also benefit from the assistance of similar independent intermediary organisations. Boundary organisation theory is used to compare organisations' structures and working practices against the characteristics of successful independent intermediary negotiating organisations. It is concluded that the boundary organisation theory framework can be usefully applied to identify organisational strengths and weaknesses, and to assess competences to assume the role of an independent intermediary negotiating organisation.